PENGARUH KUALITAS PELAYANAN DAN NILAI PRODUK TERHADAP KEPUASAN PENGUNJUNG DI MUSEUM POS INDONESIA BANDUNG - Liliana Dewi (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
This research is about the influence of service quality and product value on customer satisfaction at Museum Pos Indonesia Bandung. There are two indicators, service quality and product value as independent variables, and customer satisfaction as dependent variable. Using quantitative descriptive method to know the influence of service quality and product value on customer satisfaction. Through primer data, observation, questionnaire and theories support for achieving this research’s goal. Conclusion of this research is there is influence of service quality and product value on customer satisfaction at Museum Pos Indonesia Bandung. Coefficient correlation shows there is a strong correlation between these variables. Significant test F Test shows there are significant coefficient multiple correlation.